TRANSLATING METHOD TOWARDS SEXISM IN ENGLISH VERSION OF ANDMESH SONG TITLED “HANYA RINDU” - Safitri, Rizka (Language Horizon: Journal of Language Studies, 2021)
The topic in this study contins the translation works on Andmesh song titled “Hanya Rindu” in English version by Emma Heester and Kurt Hugo Schneider. Using a descriptive qualitative method by doing documentation to identify the genderlect of Andmesh song titled “Hanya Rindu” and the translation methods applied in English version of the song translated by Emma Heesters and Kurt Hugo Schneider. Moreover, this study is constructed under the theory of the distinction of language used between men and women by Tannen (1990), the differences of writing styles between men and women by Hallidays (1994) and the translation method by Newmark (1988). Deborah Tannen proposed 6 distinction of language used by men and women which are status vs support, independence vs intimacy, advice vs understanding, information vs feelings, orders vs proposal, and conflict vs compromise. Also, Halliday stated that in term of writing styles, men are more informative while women are more ‘involve’. In addition, Peter Newmark divides translation methods in 2 divisions of translation methods based on source language emphasis and target language emphasis which are word-for-word translation, literal translation, faithful translation, semantic translation, adaptation, free translation, idiomatic translation and communicative translation. The findings reveal that there are only 3 distinction of language used by Emma and Kurt which are status vs support, information vs feelings and orders vs proposal. Besides, Emma translation works is more ‘involve’ while Kurt translation works is more informative. Additionally, both Emma and Kurt are using semantic and faithful translation works to transfer the message from the source language to the target language. In short, Emma and Kurt translation works are different in term of interpreting the message from the source language to the target language and their writing styles.